Rod Phototransduction Determines the Trade-Off of Temporal Integration and Speed of Vision in Dark-Adapted Toads - Haldin, Charlotte (J Neurosci, 2009)
Human vision is ∼10 times less sensitive than toad vision on a cool night. Here, we investigate (1) how far differences in the capacity for temporal integration underlie such differences in sensitivity and (2) whether the response kinetics of the rod photoreceptors can explain temporal integration at the behavioral level. The toad was studied as a model that allows experimentation at different body temperatures. Sensitivity, integration time, and temporal accuracy of vision were measured psychophysically by recording snapping at worm dummies moving at different velocities. Rod photoresponses were studied by ERG recording across the isolated retina. In both types of experiments, the general timescale of vision was varied by using two temperatures, 15 and 25°C. Behavioral integration times were 4.3 s at 15°C and 0.9 s at 25°C, and rod integration times were 4.2–4.3 s at 15°C and 1.0–1.3 s at 25°C. Maximal behavioral sensitivity was fivefold lower at 25°C than at 15°C, which can be accounted for by inability of the “warm” toads to integrate light over longer times than the rods. However, the long integration time at 15°C, allowing high sensitivity, degraded the accuracy of snapping toward quickly moving worms. We conclude that temporal integration explains a considerable part of all variation in absolute visual sensitivity. The strong correlation between rods and behavior suggests that the integration time of dark-adapted vision is set by rod phototransduction at the input to the visual system. This implies that there is an inexorable trade-off between temporal integration and resolution.